2022
DOI: 10.20945/2359-3997000000476
|View full text |Cite
|
Sign up to set email alerts
|

Molecular signature of immunological mechanism behind impaired endometrial receptivity in polycystic ovarian syndrome

Abstract: Objective: Despite the treatment of anovulation, infertility is still one of the main complications in PCOS women during reproductive age, which appears to be mainly due to impaired uterine receptivity. This study investigated the transcriptome profiles of endometrium in PCOS patients and healthy fertile individuals as the control group. Material and methods: Total mRNA was extracted from endometrial tissues of PCOS patients (n = 12) and healthy fertile individuals (n = 10) during the luteal phase. After cDNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
1
0
Order By: Relevance
“…In women suffering PCOS, endometrial receptivity has been postulated to be affected via several mechanisms: (1) sustained androgenic exposure due to the abberant hormonal milieu [69,70], (2) metabolic alterations that regulate decidualization [71], (3) compromised PR functions led to total failure of the uterus in supporting embryo implantation [72], and (4) altered intrauterine microenvironment via deregulation of local inflammatory mediators [73,74]. In clinical practice, PCOS is related to a higher risk of miscarriage and adverse pregnancy outcomes [75], though its effect on IVF and FET cycles remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…In women suffering PCOS, endometrial receptivity has been postulated to be affected via several mechanisms: (1) sustained androgenic exposure due to the abberant hormonal milieu [69,70], (2) metabolic alterations that regulate decidualization [71], (3) compromised PR functions led to total failure of the uterus in supporting embryo implantation [72], and (4) altered intrauterine microenvironment via deregulation of local inflammatory mediators [73,74]. In clinical practice, PCOS is related to a higher risk of miscarriage and adverse pregnancy outcomes [75], though its effect on IVF and FET cycles remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Any dysregulation in MMPs is associated with scarring and fibrosis in inflammation and wound healing. A study investigating the transcriptome profile of endometrium in PCOS showed significantly lower expression of MMP7 in PCOS compared to healthy controls [ 69 ]. The inflammatory environment inherent to PCOS could potentially cause loss of the association of MMP7 with 25(OH)D 3 in these non-obese PCOS subjects.…”
Section: Discussionmentioning
confidence: 99%